Zeolitic imidazolate framework (ZIF-8) modified cellulose acetate NF membranes for potential water treatment application. (1st January 2023) - Vatanpour, Vahid; Yuksekdag, Ayse; Ağtaş, Meltem; Mehrabi, Mohammad; Salehi, Ehsan; Castro-Muñoz, Roberto; Koyuncu, Ismail
Abstract: In this study, cellulose acetate (CA)-based nanofiltration membranes, modified with zeolitic imidazole framework-8 (ZIF-8) particles, were prepared with various ZIF-8 contents (0, 0.1, 0.25, 0.5, 1 and 2 wt%), to obtain membranes with improved flux and filtration performance by combining advantages of CA polymer and ZIF-8 metal-organic frameworks. Removal efficiency studies were carried out with bovine serum albumin and two different dyes, along with antifouling performance evaluation. Results of experiments disclosed that as the ZIF-8 ratio increased, the contact angle values decreased. With ZIF-8 addition, the pure water flux of the membranes increased. Besides, the flux recovery ratio value was approximately 85 % for the bare CA membrane, while it increased to above 90 % by blending ZIF-8. Also, in all ZIF-8 doped membranes, a fouling decrease was observed. Importantly, it was observed that the dye removal efficiency increased with the addition of ZIF-8 particles from 95.2 to 97.7 % for Reactive Black 5 dye. Graphical abstract: Unlabelled Image Highlights: Modification of cellulose acetate UF membranes with ZIF-8 MOF nanoparticles. Improving permeability, rejection and antifouling properties by ZIF-8 blending. Blending of ZIF-8 improved fouling resistance ratio from 85 % to above 90 %. Reactive Black 5 dye rejection increased from 95.2 to 97.7 % by ZIF-8 addition.